Legal Analysis of the Criminal Act of Online Togel Gambling in Dirokan Hilir (Study of Decision No. 296/PID.B/2024/PN-RHL) - Rizki Ramadhan Pery; Risdalina Risdalina; Kusno Kusno (International Journal of Science and Environment (IJSE), 2026)
The development of digital technology has led to an increase in online gambling practices in Indonesia. This article discusses a legal analysis of online gambling crimes based on Decision Number 296/Pid.B/2024/PN Rokan Hilir, in which the defendant Marihot Sitinjak was charged and sentenced for his actions as an online lottery bookie. This research uses a normative legal method based on court decision data. The results of the study show that the panel of judges stated that the defendant was legally and convincingly proven to have violated Article 303 paragraph (1) point 1 of the Criminal Code for offering and providing opportunities for gambling as a livelihood. This decision confirms the consistency of the application of the law to online gambling practices that are rampant in society. The Decision of the Rokan Hilir District Court Number 296/Pid.B/2024/PN Rhl stated that the defendant Marihot Sitinjak was proven guilty of conducting online lottery gambling as a livelihood, with a prison sentence of 1 year and 8 months based on Article 303 paragraph (1) point 1 of the Criminal Code. This verdict was issued on August 22, 2024, by the Panel of Judges led by Ahmad Rizal, SH, MH, after examining the Public Prosecutor's alternative charges and trial evidence.